Assessing the acceptance and behavioral intentions towards ChatGPT among undergraduate students/ Mohammad Fazli Baharuddin ... [et al.] - Baharuddin, Mohammad Fazli; Ahmad Zaki, Nur Diyanah; Mohammad Yusuff, Khairun Nizam; Wahi Anuar, Muhammad Asyraf (Universiti Teknologi MARA Cawangan Selangor, 2024)
The application of artificial intelligence (AI) in education will grow in the future as technology advances. By looking for a new research setting, the relationship between performance expectancy, effort expectancy, social in-fluence, facilitating conditions and behavioural intention towards ChatGPT of selected undergraduate students in Malaysia is the central theme for this study. This study was conducted throughout Malaysia with a total of 218 valid questionnaires were obtained from selected undergraduate student in Malaysia. Findings of the study show that relationship between performance expectancy, effort expectancy, social influence, facilitating conditions and behavioural intention towards ChatGPT are significant. This research can be extended by more investigations and analysis of the many variables, as well as exploring other potential areas of inquiry.